Local food concept in self sufficient producer in Malaysia - Yusoff, Noraniza; A., Abdul Azis; A. R., Abdul Razak; D., Andrian (2013)
Local food means food produced in the same province in which it’s sold or food sold across provincial borders within 50 kilometres of the originating province or territory.There is no consistent definition of “local food”.The purposes of this analysis includes (a) to distinguish between the defining attributes of local food concept and its irrelevant structure and (b) to determine its internal structure by breaking it into simpler elements.The Wilson concept analysis was employed for analysis.Result showed that local food concept differs from halal food concept.Halal food refers to hygiene and healthy foods accord with the teachings of the Quran and Sunnah of the Prophet, Ijma’ (consensus) and Qiyas (deduction of analogy according to the Syafie or any one of the Hanafi, Maliki or Hanbali School of thought or fatwa approved by the relevant Islamic Authority).While, paddy in 1970-1980 met about 87% of the domestic need the result of government policy that emphasised higher food self-sufficiency by increasing yields.In paddy sector, Ninamaju Sdn Bhd is a rice producer started its operation since 1981 originated from and located at northern part of Malaysia or the rice bowl of Malaysia, Kedah.Involved in the production of high quality rice and processing using high-tech machines to meet the demands of daily food community.